Implementation of an Integrated Pre-Tahfiz Model for Developing Religious Values in Early Childhood Education: A Case Study at Tadika Ceria Az-Zahra Malaysia - Nurul Novitasari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This study explores the implementation of an integrated pre-Tahfiz model in early childhood education and its contribution to developing religious values among young learners at Tadika Ceria Az-Zahra, Malaysia. In response to the growing need for holistic Islamic-based education at the preschool level, the pre-Tahfiz program integrates Qur’anic memorization with character-building activities rooted in Islamic teachings. Using a qualitative case study approach, data were collected through observation, semi-structured interviews with teachers and parents, and documentation of daily classroom activities. The results indicate that structured and engaging memorization sessions, combined with consistent reinforcement of religious practices such as prayer, dua recitation, and Islamic storytelling, significantly enhance children’s spiritual awareness and behavioral discipline. Furthermore, the study highlights the vital role of parental involvement in reinforcing learning outcomes at home. Parents who actively participate in their children’s Qur’anic learning tend to foster stronger religious values and emotional bonds. The integrated pre-Tahfiz model at Tadika Ceria Az-Zahra is found to be effective not only in improving children’s memorization skills but also in nurturing respect, responsibility, and a love for Islam from an early age. This model can serve as a reference for other early childhood institutions seeking to combine academic and spiritual development through early Qur’anic education. The findings support the importance of collaborative efforts between educators and parents in shaping the religious character of young Muslim learners.